Peasant Agriculture and Economic Growth: The Case of Southeast Europe c. 1870-1940 reinterpreted - Michael Kopsidis (European Historical Economics Society (EHES), 2012)
Still in recent research a low productive peasant economy and traditional peasant society are often made responsible for Southeast Europe's economic backwardness prior to 1945. However, the radical change of paradigm after 1960 in the view of peasants as agents of economic growth and of their ability to adjust to markets has surprisingly never been realized in economic history research on the Balkan-states (Romania, Bulgaria, Yugoslavia, Greece). Interpreting agricultural development as a mainly demand-driven process this paper argues that the potential for agricultural growth was much more restricted in Southeast than in Northwest Europe but Balkan peasants seem to have exploited their growth potential as far as possible. There is a lot of evidence that the reasons for sluggish growth before 1940 were definitely not rooted in any 'peasant traditionalism' as often claimed by Balkan elites and many scholars.
Keywords: N53; N54; O13; 330; Romania; Bulgaria; Yugoslavia; Greece; agricultural development; peasant economy